2019
DOI: 10.3390/ijerph16245142
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Emotional Environmental Pictures on Behavior Intentions: The Evidence of Neuroscience Technology

Abstract: Background: In recent years, researchers have been paying increasing attention to the issues of how emotions affect people’s perceptions of the environment, and how they influence people’s behavior or intentions to act. The purpose of this study is to explore the influences of emotions on environmental intention to act by using the neuroscience technology electroencephalography (EEG). Methods: A total of 70 university students participated in this study. They looked at positive and negative emotional environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…For example, Graham-Rowe et al (2015) found that anticipating regret helps predict residents’ intentions to reduce household food waste. Later, Chang et al( 2019 ) used evidence in neuroscience technology to show that negative environmental affective reactions caused by viewing negative environmental pictures (such as cracked land) were significantly positively correlated with pro-environmental behavioral intentions. Recently, Salem et al (2020) affirmed the role of affective reactions in an individual's garbage collection behaviors.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…For example, Graham-Rowe et al (2015) found that anticipating regret helps predict residents’ intentions to reduce household food waste. Later, Chang et al( 2019 ) used evidence in neuroscience technology to show that negative environmental affective reactions caused by viewing negative environmental pictures (such as cracked land) were significantly positively correlated with pro-environmental behavioral intentions. Recently, Salem et al (2020) affirmed the role of affective reactions in an individual's garbage collection behaviors.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…The duration of the exposure of the EEG stimuli varies across authors. Yasuhisa et al (2020) exposed each image stimulus for 6 seconds [ 67 ], whereas Wei-Yin et al (2019) presented 60 photos at random for 20 seconds [ 68 ]. Agnieszka et al (2018) presented 36 images at random for 10 seconds [ 41 ].…”
Section: Experiments and Analysismentioning
confidence: 99%
“…Affective reactions are emotions or moods experienced resulting from the assessment of the external environment (Chang et al, 2019 ). Humanity has greatly suffered from the COVID‐19 pandemic, causing serious psychological distress and producing adverse environmental affective reactions.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Affective reactions are emotions or moods experienced resulting from the assessment of the external environment (Chang et al, 2019).…”
Section: Moderated Effect Of Nearmentioning
confidence: 99%
See 1 more Smart Citation